A Christian Amulet Containing Colossians 3:9-10 - Wayment, Thomas (Vigiliae Christianae, 2015)
This article presents the editio princeps and a brief discussion of a Christian amulet that preserves Colossians 3:9-10 in Greek on papyrus. The amulet was discovered at Oxyrhynchus by W.M. Flinders Petrie and is currently housed in the Petrie Egyptian Museum in London. This is currently the first amulet to preserve a passage from Colossians in Greek and it appears that the amulet served as an aide mémoire to the person wearing it to remind the person of the meaning of Christian baptism.